Cost estimates of production scale semitransparent organic photovoltaic modules for building integrated photovoltaics. Issue 11 (2nd October 2020) - Lee, Byungjun; Lahann, Lucas; Li, Yongxi; Forrest, Stephen R.
Abstract : Building integrated photovoltaics (BIPVs) are attached to commercial and residential structures to enable solar energy harvesting. Abstract : Building integrated photovoltaics (BIPVs) are attached to commercial and residential structures to enable solar energy harvesting. While conventional Si photovoltaics (PVs) are dominant in the current market, second and third generation thin film solar cells based on amorphous Si, CdTe, CIGS, perovskites or organic photovoltaics (OPVs) are often considered as an alternative for BIPV applications since they may offer reduced costs compared to Si PVs. Indeed, recent advances in performance suggest that lightweight, flexible and visibly transparent OPVs can potentially be integrated into windows or other applications to which Si PVs are less well suited. Here, we estimate the cost of high efficiency, semitransparent OPVs (ST-OPVs) based on solution processing in a roll-to-roll (R2R) manufacturing line. Assuming modules with 10% power conversion efficiency (PCE), a 70% geometric fill factor (GFF), and 95% inverter efficiency, we anticipate a %1.6 per Wp module manufacturing cost that includes the cost of the microinverter to condition the OPV dc output to be compatible with the ac line voltage of the building. The materials and inverter cost comprise ∼90% of the total module cost. Hence, with simplified material synthesis and a lower inverter cost, including marginally improved PCE and GFF, we expect the cost can be as low as 0.47 per Wp . While the module costs ∼60% of the average (uninstalled) double-pane window, we expect the payback period can be as short as 2 to 6 years, suggesting that OPVs can be an economic and attractive candidate for BIPV applications.